Electrolytic Cleaning as Part of Surgical Reconstructive Peri-Implantitis Treatment: A Case Series - Jarno Hakkers; Henny J. A. Meijer; Yvonne C. M. de Waal; Gerry M. Raghoebar (Dentistry Journal, 2025)
Background/Objectives: The aim of this study was to assess the workflow and evaluate the clinical, radiographic and patient-reported outcome measures of surgical reconstructive peri-implantitis treatment aided with an electrolytic cleaning device. Methods: This case series describes three patients that presented with peri-implantitis surrounding an implant in the anterior maxilla, eligible for surgical reconstructive peri-implantitis treatment. The implant crown was removed, and the patients were surgically treated during which an electrolytic cleaning device was used to clean the implant surface. Thereafter, the implant site was augmented using locally harvested bone and a bovine bone substitute. After 6 months of submerged healing, the implant crown was replaced. Follow-up visits were performed 3 and 6 months after restoration placement. Clinical and radiographical parameters, as well as Patient-Reported Outcome Measures (PROMs) and Pink Esthetic Scores (PESs) were collected. Results: The data collected indicate a positive trend with regard to peri-implant pocket depth, bleeding and suppuration scores, as well as the peri-implant marginal bone level for the evaluated cases six months postoperatively. PROMs with regard to pain experience varied between 4.5 and 5.9 on the Visual Analogue Scale (VAS). After 12 months, the PES increased in two cases and decreased in one case. Conclusions: This case series provides a comprehensive overview of the surgical reconstructive peri-implantitis treatment using an electrolytic cleaning device, highlighting promising results with regard to the aforementioned parameters.